Ireland's industrial policy in an integrated global economy : the case of the Celtic Tiger in the 1990s - Casey, Bronagh (Department of Political Studies, 2014)
The research of this paper focuses on Ireland's economic development in the 1990s. The central question of this paper is to demonstrate how the Irish government developed an industrial strategy that would create and attract a large amount of Foreign Direct Investment. (FDI), Two critical concepts serve as analytical focal points. Firstly I look at economic globalization and the debate surrounding the sovereignty of the nation-state. I set up as the null hypothesis the liberalist assumption that the nation-state is in demise, and have to surrender its power to global market forces. The alternative hypothesis. the mercantilist perspective. argues that the state is not in demise and is still the primary actor in the international system. In this regard, I look at Irish government policy and the degree of influence in economic development from 1987-2000. The second concept focuses around industrial policy. This includes the participation of state institutions in industrial strategy. such as the Industrial Development Authority. I also focus on the model that the Irish government followed in order to pursue FDI. The 'Closed Loop' model consists of three stages: firstly. to select industry areas offering the best economic returns; second, to find the best companies in those industry areas: and third. to persuade their target companies to invest in Ireland. Industrial policy includes the range of incentives and policy decisions the government undertook in order to attract Multinationals to Ireland. This includes policy decisions on areas such as education, tax, infrastructure. wages and spending of structural funds. Through a literature review of the two concepts regarding Ireland's growth. I conclude that the Irish government has been deeply involved in the entire process of integration. This paper supports the mercantilist hypothesis that the state still remains the primary actor in the international economy. It also supports the view that the state can manipulate and exploit globalization in order to maximize its own interests. Irish economic development in the 1990s is a prime example of this.